Penyelesaian Tindak Pidana Melalui Mediasi Penal pada Tingkat Penuntutan berdasarkan Peraturan Kejaksaan Nomor 15 Tahun 2020 Tentang Penghentian Penuntutan Berdasarkan Keadilan Restoratif (Studi Pada Kejaksaan Negeri Sijunjung) - Ghifari, Teguh; Zurnetti, Aria; Yasniwati, Yasniwati (Dinasti Research, 2025)
The development of criminal law has encouraged the implementation of penal mediation as an alternative for resolving criminal cases. This study aims to analyze: (1) the resolution of criminal acts through penal mediation based on the Attorney General Regulation Number 15 of 2020 at the prosecution level in Sijunjung District Attorney’s Office; (2) the considerations for appointing a Facilitator Prosecutor within the Restorative Justice framework; and (3) the obstacles in implementing penal mediation. This research employs an empirical legal (sociological) approach with a descriptive method. The findings indicate that the Public Prosecutor acts as a third party facilitating deliberations between the victim and the offender until an agreement is reached; the appointment of a Facilitator Prosecutor considers integrity, competence, communication skills, experience, and caseload; and the main obstacles include negative public perceptions of case termination, limited public understanding of restorative justice, and a short duration for peace-making processes. The study highlights the crucial role of Prosecutors in supporting criminal case resolution through penal mediation.